Macroeconomic fluctuations, economic policy and the Jamaican stock market (1991-1999) - Bailey, Karlene (2001)
Analyses the effects of monetary and fiscal policy on the behaviour of Jamaican stock prices within the framework of a dynamic model, which utilises the Vector Autogressive methodology.